Healing Rates of Venous Leg Ulcer Using Four Layer Bandage and Short Stretch Bandage- A Comparative Study in Aspect of Bangladesh - Hasan, Rakibul; Khan, Md Saif Ullah; Mahmud, Mainul; Saha, Samaresh Chandra; Bhowmick, Sourav (University Heart Journal, 2020)
Background: Chronic venous leg ulcer is one of the common medical conditions encounter by the vascular surgeons in Bangladesh. Many of these patients develop venous leg ulcer as a sequel of the disease. In advance chronic venous disease such as development of ulcer, single or multilayer dressings are usually used. Objective: To find out a compression therapy (single layer crepe/short stretch bandage and multilayer/four layer bandage) in patients with venous leg ulcer. Materiel & Methods: This study was conducted on 200 patients with in last two years, march 2017 to february 2019 at Bangabandhu Sheikh Mujib Medical University (BSMMU), Department of vascular surgery. In which 100 patients with venous leg ulcer where treated with four layer bandage and another 100 patients with same condition were treated with single layer crepe bandage. Before application of bandage, proper history of patient was taken and duplex scan was done. The primary outcome was measured by time duration of ulcer healing. Secondary outcome included incidence and number of adverse events in every patient. Results: Healing time of venous ulcers was accessed with periodic interval. The four layer bandage was associated with significantly shorter time of healing. P value reached from unpaired t-test. Primary outcome shows 68% of patients who received four layer bandages achieved healing within one month. On the other hand, 12% of patients who received single layer/crepe bandage did so. Conclusion: Four layer bandages heals venous leg ulcer more rapidly than the single layer crape bandage. These data suggest that the benefits observed the consistent despite prognosis is different. Patients with large ulcers have poor healing prognosis regardless of its treatment modalities. University Heart Journal Vol. 16, No. 2, Jul 2020; 78-85